AKUNTABILITAS PENGELOLAAN DANA DESA - Tuti Dharmawati; Mulyati Akib; Satira Yusuf (Fakultas Tarbiyah dan Ilmu Keguruan, IAI Sultan Muhammad Syafiuddin, 2021)
The research aims to analyze the accountability of the palnning, implementation and responsibility of Rompu-Rompu village fund management in North Poleang district of Bombana regency from 2015 until 2016. The samples were 3 (three) Rompu-Rompu village administrators and the head of North Poleang district that were connsidered to represent the study of the village fund management. The analysis method was quantitative with descriptive qualitative approach which studying through data analysis and all kind of informations derived from the samples which were rational and empirical. The result showed that village administration accountability in the Rompu-Rompu village fund management has been in line with the ministry of home affair regulation number 113 year 2014. Started from the mechanism/procedure on planning, arrangement, presentation, as well as the distribution of APBDesa (Anggaran Pendapatan dan Belanja Desa) and activities implementation from 2015 until 2016 were already based on art and law regulation. The physical from of had shown the accountable and transparent implementation. However, there’s still a need to improve the administration accountability for the betterment of accountability principle application.